American Marxism - Levin, Mark R. (Mark Reed), 1957- (New York : Threshold Editions, 2021)
"In 2009, Mark R. Levin galvanized conservatives with his unforgettable manifesto Liberty and Tyranny, by providing a philosophical, historical, and practical framework for halting the liberal assault on Constitution-based values. That book was about standing at the precipice of progressivism's threat to our freedom and now, over a decade later, we're fully over that precipice and paying the price. In American Marxism, Levin explains how the core elements of Marxist ideology are now pervasive in American society and culture"--
Levin explains how the core elements of Marxist ideology are now pervasive in American society and culture: from our schools, the press, and corporations, to Hollywood, the Democratic Party, and the Biden presidency. Often cloaked in deceptive labels like "progressivism" tactics of Marxism include the widespread brainwashing of students, the anti-American purposes of Critical Race Theory and the Green New Deal, and the escalation of repression and censorship to silence opposing voices and enforce conformity. Levin exposes many of the institutions, intellectuals, scholars, and activists who are leading this revolution-- and provides ideas on how to confront them. -- adapted from jacket
It's here -- Breeding mobs -- Hate America, Inc. -- Racism, Genderism, and Marxism -- "Climate Change" fanaticism -- Propaganda, censorship, and subversion -- 'We choose liberty!'
Includes bibliographical notes (pages [279]-309).
109023
Keywords: Political culture -- United States; Socialism -- Political aspects -- United States; Communism -- Political aspects -- United States; Opinion (Philosophy) -- Political aspects -- United States; United States -- Politics and government -- 21st century; Political science